1991
DOI: 10.1007/bf01756387
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of integrins in adhesion of human colonic carcinoma cells to extracellular matrix components

Abstract: We have examined integrin expression and function in the human colon carcinoma cell line HT29, and in clonal sublines derived from the HT29 line. These cells express several different integrin subunits including beta 1, alpha 2, 3, 6 and alpha v, but do not express the classic alpha 5/beta 1 fibronectin receptor. Clonal variation in the pattern of integrin expression was quite limited. The profile of integrin expression correlates well with the adhesive behavior of HT29 cells. Thus the cells adhere well to vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 55 publications
3
26
2
1
Order By: Relevance
“…Using other subclones of HT-29 cells, Danecker et al (1989) found similar differences in the adhesion behaviour of colorectal carcinoma cells, with poorly differentiated cell clones adhering better to FN. In contrast to other studies (Schreiner et al, 1991;Lehmann et al, 1994;Herzberg et al, 1996), we detected little or no adhesion of HT-29P cells to FN or VN under the conditions used for the adhesion assays. In previous studies with the HT-29LMM subclone, a higher rate of adhesion to liver endothelial cells was demonstrated compared to endothelial cells derived from lung (Sawada et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Using other subclones of HT-29 cells, Danecker et al (1989) found similar differences in the adhesion behaviour of colorectal carcinoma cells, with poorly differentiated cell clones adhering better to FN. In contrast to other studies (Schreiner et al, 1991;Lehmann et al, 1994;Herzberg et al, 1996), we detected little or no adhesion of HT-29P cells to FN or VN under the conditions used for the adhesion assays. In previous studies with the HT-29LMM subclone, a higher rate of adhesion to liver endothelial cells was demonstrated compared to endothelial cells derived from lung (Sawada et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…Previously it has been shown that the integrin expression of HT-29 cells was also independent from the state of differentiation of these cells (Schreiner et al, 1991). The moderate adhesion to LN was not mediated by the α 6 β 4 -integrin.…”
Section: Discussionmentioning
confidence: 77%
“…The alpha6beta4 integrin was first reported as a laminin receptor in intestinal cells working in cooperation with another beta1 integrin, most likely alpha2beta1 (107,111,112). In hemidesmosome-expressing cells such as those at the epidermal-mesenchymal interface, alpha6beta4 plays an essential role in the assembly and for the stability of hemidesmosomes while it mediates anchorage on laminin-5 in cooperation with alpha3beta1 (113)(114)(115).…”
Section: Alpha6beta4mentioning
confidence: 99%
“…14 However, only a few human colon cancer cell lines are known to express this integrin. 14,16,17 Recently, Livant et al 15 demonstrated that a small peptide antagonist (amino-acid sequence PHSCN) to integrin ␣ 5 ␤ 1 significantly reduced neovascularization and formation of metastases in an animal model of prostate carcinoma that expresses integrin ␣ 5 ␤ 1 .…”
mentioning
confidence: 99%